596 Can Improved Awareness of Intersectionality in Surgery Make Us Better Allies to Female Surgeons?. (19th August 2022) - Abdul Kader, N; Morrison, TEM; Islam, R; Suresh, S; Palepa, A; Mohamed, S; Gooch, D; Burns, S; Dixon, S; ,
Abstract: Aim: Presently, 38% of trainees and 14% of Surgical Consultants are female. Despite progression from 3% female Consultant Surgeons in 1991, with over 50% of medical students now identifying as female, gender equality in Surgery still lags. While female surgeons may share this minority intersection and statistic, the experience of every female surgeon is unique. Therefore, while we seek gender equality, it is important to consider the role of intersectionality and how the simultaneous possession of other under-represented characteristics may present significant barriers to female surgeons. Method: Female surgeons of various grades were approached about their experiences and barriers they have faced as women in surgery. Additionally, healthcare providers were asked for their opinions on how we can be effective allies to female surgeons. Results: Positive use of power and privilege, equitable access to opportunities, mentorship and professional, personal or peer support were cited as important contributors. The importance of cultural competency, creating an inclusive environment of mutual respect, avoiding assumptions, addressing bias, listening to the barriers to progress and experiences of women in surgery, improving adaptability of the workplace, self-education, raising the profile of organisations who support the progression of female surgeons and normalising the place of women in leadership positions were quoted. Conclusion: To achieve effective allyship, as well as identifying shared needs and concerns, we must acknowledge and embrace individual differences and recognise that everybody has different starting blocks. More research is needed on the barriers for and outcomes of female surgeons who possess under-represented characteristics.